2011
DOI: 10.1029/2010jd015544
|View full text |Cite
|
Sign up to set email alerts
|

Long-term development of short-period gravity waves in middle Europe

Abstract: [1] The long-term development of short-period gravity waves is investigated using the analysis of temperature fluctuations in the mesosphere. The temperature fluctuations are quantified by their standard deviations s based on data from OH measurements at Wuppertal (51°N, 7°E) and Hohenpeissenberg (48°N, 11°E) obtained from 1994 to 2009 at 87 km altitude. The temperatures are Fourier analyzed in the spectral regime of periods between 3 and 10 min. The resulting oscillation amplitudes correlate very well with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 69 publications
2
6
0
Order By: Relevance
“…A trend for an increase in gravity wave amplitude has been reported through observations of the gravity wave kinetic energy from both medium frequency and meteor radars through horizontal wind measurements (Hoffmann et al, 2011) at midlatitudes. Other studies have also shown a tendency for the gravity wave activity to increase in the mesosphere and lower thermosphere region (e.g., Offermann et al, 2011;Oliver et al, 2013). It has also been observed from our data that the mean zonal wind during the same period shows an increasing trend at a rate of about 69 ± 24 m/yr (figure not shown here).…”
Section: Possible Connection To Changing Gravity Wave Fluxessupporting
confidence: 88%
“…A trend for an increase in gravity wave amplitude has been reported through observations of the gravity wave kinetic energy from both medium frequency and meteor radars through horizontal wind measurements (Hoffmann et al, 2011) at midlatitudes. Other studies have also shown a tendency for the gravity wave activity to increase in the mesosphere and lower thermosphere region (e.g., Offermann et al, 2011;Oliver et al, 2013). It has also been observed from our data that the mean zonal wind during the same period shows an increasing trend at a rate of about 69 ± 24 m/yr (figure not shown here).…”
Section: Possible Connection To Changing Gravity Wave Fluxessupporting
confidence: 88%
“…It shows a slope of 4.7%/yr (for year 2000, chosen to match reference year chosen for the corresponding calculation with the Hoffmann et al [] data). This compares with the 1.5%/yr reported by Offermann et al [] and the 2–6%/yr computed from the data of Hoffmann et al [] for mesospheric temperature and winds. There are also decadal fluctuations in the GW proxy.…”
Section: Development Of a Gravity Wave Proxysupporting
confidence: 86%
“…Offermann et al [] note that as of year 2011, no conclusive results appear to be available on the long‐term trend in gravity wave activity. They developed a gravity wave (GW) proxy for their mesospheric temperature measurements in terms of the standard deviation about the mean for a given time interval.…”
Section: Development Of a Gravity Wave Proxymentioning
confidence: 99%
“…Long‐term trends in winds [e.g., Sridharan et al , 2007; Merzlyakov et al , 2009; Jacobi et al , 2012] and tides [e.g., Vincent et al , 1998; Tsuda et al , 1999; Hagan and Forbes , 2002; Oberheide et al , 2009] are found to vary with location and period of observation. Long‐term studies of gravity wave activity show inter‐annual variability [e.g., Tsuda et al , 2002] and increasing trend [ Offermann et al , 2011; Hoffmann et al , 2011]. Recent studies attempt to summarize decadal variability and trends of the atmospheric parameters in order to get a comprehensive global picture [e.g., Beig et al , 2008].…”
Section: Introductionmentioning
confidence: 99%